Kajian dampak lingkungan pada sistem produksi listrik dari limbah buah menggunakan life cycle assessment - Fajar Marendra; Anggun Rahmada; Agus Prasetya; Rochim B. Cahyono; Teguh Ariyanto (Jurnal Rekayasa Proses, 2018)
Producing biogas by anaerobic digestion (AD) is a promising process that can simultaneously provide renewable energy and dispose solid waste safely. However, this process could affect environment e.g. due to greenhouse gas emissions. By life cycle assessment (LCA), we assessed the environmental impact (EI) of an integrated fruit waste-based biogas system and its subsystems of Biogas Power Plant Gamping. Data were collected from an actual plant in Gamping, Sleman, Yogyakarta, Indonesia that adopted a wet AD process at mesophilic condition. The results showed that the global warming potential (GWP) emission of the system reached 81.95 kgCO2-eq/t, and the acidification potential (AP), eutrophication potential (EP), human toxicity potential (HTPinf) and fresh water ecotoxicity (FAETPinf) emissions were low. The EI was mainly generated by two subsystems, namely, the electricity generation and the digestate storage. A comparison analysis showed that the GWP become the main contributor of environmental loads produced by Biogas Plant Gamping, Suazhou Biogas Model, Opatokun Biogas Model, Opatokun Pyrolisis Model, dan Opatokun Integrated System Anaerobic Digestion and Pyrolisis. The GWP impact control and reduction could significantly reduce the EI of the system. It has been shown that improving the technology of the process, the electricity generation and the digestate storage will result in the reduction of EI of the biogas system.